SIKAP REMAJA PUTRI TERHADAP PENDEWASAAN USIA PERKAWINAN - Rita Ariesta (Akademi Kebidanan La Tansa Mashiro, 2013)
This article discusses the attitude teenagers of marriageable age to maturity in terms of socioeconomic factors, educational factors, parental factors. KB as one program whose objective population control program trigger Maturation Age Marriage (PUP). Family as the smallest unit of society in which there is a parent figure as a role model would have an important role to form toward the adolescent mind and a great effect for adolescent development given first place for the growing family the development and formation of the right mindset. The need to perform a marriage laws and also reinforce existing laws crucial to supporting the success of this effort. Cooperation of related organizations (BKKBN) and community organizations are youth clubs, school recitals and agencies can be a means of delivering information to support the attitude teenagers of marriageable age to maturity.